Designing the structure of a multi-textured flax-containing fabric - Natallia S. Akindzinava (Vestnik of Vitebsk State Technological University)
Currently, synthetic household materials with multi-dense areas and a combination of different textures in one fabric are widely used. This design approach aligns with contemporary fashion trends. At the same time, the Republic of Belarus has a sufficient raw material base, extensive technical capabilities and scientific groundwork for the development and implementation of technologies for the manufacture of natural flax-containing multi-dense fabrics with a multi-textured surface derived from domestic natural flax-containing raw materials. Natural materials have undeniable advantages and are appreciated all over the world, but linen fabrics generally lack high drapability, limiting their ability to form elegant folds in clothing or in home textiles. The development of structures of flax–containing fabrics consisting of sections of various layering and filling – from transparent thin to filled thickened ones – will allow not only to create multi-dense fabrics of universal use, but also entirely new textures with no existing analogues. Thanks to the introduction of new technology, it becomes possible to manufacture an import-substituting range of competitive fabrics and products, which highlights the relevance of the study.